Global Unity of the Muslim Ummah, Challenges and Solutions - Aftab Khatoon; Dr. Zain-ul-Abdin; Hafeeza Bano Arain (Journal of Religion and Society, 2025)
This paper addresses the unconstructive discourse that obliterates unity among the Muslim nations as well as offers practical solutions on the matter. The study identifies three primary obstacles: socio-economic cooperation deficits, politically charged relationships among Muslim states, and intra-religious conflicts. The sophisticated struggle toward real unity is further complicated by outside meddling, as well as competing national priorities. The analysis develops a roadmap to address these problems through institutional reforms by proposing a need to waken the OIC and other similar institutions in the Muslim world to enhance their conflict resolution capacities. It appreciates the power that Islamic financing and trading agreements for trade facilitate economic cooperation through Islamic integration. The paper also calls for greater inter- and intra-national educational and cultural initiatives aimed at narrowing the gaps created by sectarian reasoning while embracing different theological outlooks. Suggested actions also include the establishment of joint crisis management teams, launching Islamic networks for media, and formulating standard textbooks that teach shared teachings of Islam to Muslims all over the world. The study explains that unity can be attained by coordinated top-down restructuring of institutions, alongside grassroots revolution from the society led by the young, to connect the Muslim world digitally. Keywords: Muslim Unity, Islamic Cooperation, Political Integration, Economic Solidarity, Cultural Harmony